Effects of a single glucocorticoid injection on propylene glycol-treated cows with clinical ketosis. Issue 2 (May 2015) - van der Drift, Saskia G.A.; Houweling, Martin; Bouman, Marina; Koets, Ad P.; Tielens, Aloysius G.M.; Nielen, Mirjam; Jorritsma, Ruurd
Highlights: Two treatments for clinical ketosis in dairy cows were compared. Ketotic cows received propylene glycol and a glucocorticoid or saline injection. Plasma β-hydroxybutyrate concentrations were lower in glucocorticoid-treated cows. Plasma glucose concentrations increased more when cows received glucocorticoids. Glucocorticoids do not increase lipolysis in adipose tissue of ketotic cows. Abstract: This study investigated the metabolic effects of glucocorticoids when administered to propylene glycol-treated cows with clinical ketosis. Clinical ketosis was defined by depressed feed intake and milk production, and a maximal score for acetoacetate in urine. All cows received 250 mL oral propylene glycol twice daily for 3 days and were randomly assigned to a single intramuscular injection with sterile isotonic saline solution ( n = 14) or dexamethasone-21-isonicotinate ( n = 17). Metabolic blood variables were monitored for 6 days and adipose tissue variables for 3 days. β-Hydroxybutyrate (BHBA) concentrations in blood decreased in all cows during treatment, but were lower in glucocorticoid-treated cows. Cows treated with glucocorticoids had higher plasma glucose and insulin concentrations, whereas concentrations of non-esterified fatty acids, 3-methylhistidine and growth hormone were unaffected. mRNA expression of hormone-sensitive lipase, BHBA receptor and peroxisome proliferator-activated receptor type γ in adipose tissue was not affected. This shows that lipolytic effects do not appear to be important in ketotic cows when glucocorticoids are combined with PG. Plasma 3-methyl histidine concentrations were similar in both groups, suggesting that glucocorticoids did not increase muscle breakdown and that the greater rise in plasma glucose in glucocorticoid-treated cows may not be due to increased supply of glucogenic amino acids from muscle.